Effect of type of starch on the quality of fishballs - Yu, S. Y.; Yeang, S. B. (John Wiley & Sons, 1993)
Fishballs were prepared from four types of starch: native tapioca, potato and corn starches and a modified stabilized waxy maize starch. Although fish balls made from tapioca, potato and corn starches were not significantly different in terms of colour, flavour and overall acceptability, potato-starch samples scored significantly higher for texture. Texture profile analyses also showed that products containing 5% potato starch scored highest for hardness, cohesiveness, springiness, gumminess and chewiness. Of the test samples, the protein content was highest (12·30%) for fishballs containing potato starch.